Three nematode species from elasmobranchs off New Caledonia - Moravec, Frantisek; Justine, Jean-Lou (Systematic parasitology, 2006)
Nematode specimens of three species, Terranova scoliodontis (Baylis, 1931) (Ascaridida, Anisakidae), Echinocephalus sinensis Ko, 1975 and E. overstreeti Deardorff & Ko, 1983 (both Spirurida, Gnathostomatidae) were collected from the tiger shark Galeocerdo cuvier, the ray Aetobatus cf. narinari and the blotched fantail ray Taeniura meyeni, respectively, from the coastal waters of New Caledonia, South Pacific. Their examination, including scanning electron microscopy (SEM), made it possible to obtain some new data on their morphology, e.g. in relation to the number and arrangement of male caudal papillae in T. scoliodontis and both Echinocephalus spp., the presence of ventral cuticular ornamentations in T. scoliodontis and the number of transverse spines on the cephalic bulb in Echinocephalus spp. All these species are reported for the first time from New Caledonian waters and G. cuvier is a new host species for T. scoliodontis. SEM examination of the fourth-stage larvae of E. overstreeti from the type-host showed the presence of anterior dorsal and ventral groups of minute spines on the cephalic bulb to be an important taxonomic feature for the interspecific distinction of Echinocephalus larvae and questions previous data on the occurrence of E. overstreeti larvae in many elasmobranch fishes and molluscs in Australian waters.
Keywords: rejnokovití; Animals; New Caledonia; Nematoda; Female; Larva; mužské pohlaví; zvířata; hlístice; Nová Kaledonie; Male; Oceans and Seas; Sharks; Skates, Fish; oceány a moře; žraloci; ženské pohlaví; larva